The Lifshitz-Rosenzweig method in calculations of the bias of basic dislocation loops in zirconium - Trotsenko, O.G.; Babich, A.V.; Ostapchuk, P.M. (Вопросы атомной науки и техники, 2022)
Analytical expressions for the elastic interaction energy of radiation point defects of the dipole type with basic dislocation loops in zirconium are obtained for edge with Burgers vector bᴰ= 1/2 [0001] and mixed with bᴰˢ = 1/6 <2023> using Lifshitz-Rosenzweig method. They were used in numerical calculation (by the finite difference method) of the bias of these loops in a toroidal reservoir taking into account the elastic anisotropy of a hexagonal crystal. The toroidal geometry of the reservoir allows calculations for a loop of any size and without any correction of the elastic field in its area of influence. In the approximation of the center of dilatation, the dependences of the bias of loops on their radius and nature are obtained. It is suggested that bias is determined only by the edge component of its Burgers vector. The essential role of the form of the boundary condition on the outer surface of the reservoir is shown. Методом Ліфшица-Розенцвейга отримані аналітичні вирази для енергії пружної взаємодії радіаційних точкових дефектів дипольного типу з базисними дислокаційними петлями цирконію: крайової – з вектором Бюргерса bᴰ= 1/2 [0001] та – змішаної з с bᴰˢ = 1/6 <2023>. Вони були використані для чисельного розрахунку (методом кінцевих відмінностей) bias-фактора цих петель у тороїдальному резервуарі з урахуванням пружної анізотропії гексагонального кристала. Тороїдальна геометрія резервуару дозволяє проводити розрахунки для петлі будь-якого розміру і без будь-якої корекції пружного поля в області її впливу. У наближенні центра ділатації отримані залежності bias-фактора петель від їх радіуса та природи. Висловлюється припущення про те, що bias-фактор визначається тільки крайовою складовою її вектора Бюргерса. Показана суттєва роль форми граничної умови на зовнішній поверхні резервуара. Методом Лифшица-Розенцвейга получены аналитические выражения для энергии упругого взаимодействия радиационных точечных дефектов дипольного типа с базисными дислокационными петлями циркония: краевой – с вектором Бюргерса bᴰ= 1/2 [0001] и смешанной – с bᴰˢ = 1/6 <2023>. Они были использованы для численного расчета (методом конечных разностей) bias-фактора этих петель в тороидальном резервуаре с учетом упругой анизотропии гексагонального кристалла. Тороидальная геометрия резервуара позволяет провести расчеты для петли любого размера и без какой-либо коррекции упругого поля в ее области влияния. В приближении центра дилатации получены зависимости bias-фактора петель от их радиуса и природы. Высказывается предположение о том, что bias-фактор определяется только краевой составляющей ее вектора Бюргерса. Показана существенная роль формы граничного условия на внешней поверхности резервуара.